10% higher rowing power outputs after flexion-extension-cycle compared to an isolated concentric contraction in sub-elite rowers - Held, S.; Siebert, T.; Donath, L. (Frontiers in Physiology, 2020)
The resulting muscular performance is considered notably higher during a stretch shortening cycle (SSC) compared to an isolated concentric contraction. Thus, the present study examined the occurrence and magnitude of rowing performance enhancement after a flexion-extension cycle (FEC) of the legs compared to both concentric contractions only and isometric pre-contraction. Therefore, 31 sub-elite male rowers (age: 25 ± 6 years, height: 1.90 ± 0.02 m, weight: 91 ± 10 kg, weekly training volume: 11.4 ± 5.3 h/week, rowing experience: 7.1 ± 2.7 years) randomly completed (a) isolated concentric rowing strokes (DRIVE), (b) single FEC-type rowing strokes (SLIDE-DRIVE), and (c) rowing strokes with an isometric pre-contraction (ISO-DRIVE). The resulting rowing power (Prow), leg power (Pleg), and work per stroke (WPS) were recorded using motion-capturing, force, and rotation sensors. Comparison of DRIVE and SLIDE-DRIVE revealed significantly (p < 0.05) higher Prow (+11.8 ± 14.0%), Pleg (+19.6 ± 26.7%), and WPS (+9.9 ± 10.5%) during SLIDE-DRIVE. Compared to ISO-DRIVE, Pleg (+9.8 ± 26.6%) and WPS (+6.1 ± 6.7%) are again significantly (p < 0.05) higher for SLIDE-DRIVE. In conclusion, notably higher work and power outputs (compared to an isolated concentric contraction) during FEC rowing referred to an underlying SSC. Future ultrasound studies should elucidate whether a real SSC on the muscle tendon unit level account for these performance enhancements.